A COMPARATIVE ANALYSIS ON THOMAS HARDY AND ZAVERCHAND MEGHANI WITH SPECIAL REFERENCE TO STYLES AND THEMES - Prasad, Chandan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Thomas Hardy and Zaverchand Meghani both use the art of storytelling to highlight all the unique characteristics of their locale. Because of their surroundings, their characters' lives tend to follow a certain pattern. They have a destiny that is somewhat typical of the area. Only in their own region do their characters exist. Both authors of the novels are conventional storytellers. Around the fire, Hardy is ancient mariner reciting tales. It is an ancient storytelling method that is captivating and interesting. Like Hardy, Meghani wants to amuse and engage his audience by telling a captivating tale. He does not blatantly moralise or preach. Nonetheless, there is a study of human sentiments, feelings, and motivations. A comparative analysis on Thomas Hardy and Zaverchand Meghani with special reference to styles and themes has been discussed.